2020
DOI: 10.1097/rli.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Evaluation of Gadolinium Retention in Rat Brain After Single Injection of a Clinically Relevant Dose of Gadolinium-Based Contrast Agents

Abstract: The aim of this study was to investigate the presence and chemical forms of residual gadolinium (Gd) in rat brain after a single dose of Gd-based contrast agent. Methods: Four groups of healthy rats (2 sacrifice time-points, n = 10/group, 80 rats in total) were randomized to receive a single intravenous injection of 1 of the 3 Gd-based contrast agents (GBCAs) (gadoterate meglumine, gadobenate dimeglumine, or gadodiamide) or the same volume of 0.9% saline solution. The injected concentration was 0.6 mmol/kg, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Interestingly, even a single administration of a clinically‐relevant dose of GBCA demonstrated that linear GBCAs resulted in significantly higher residual Gd concentrations in the cerebellar tissue than a macrocyclic GBCA at the late timepoint of 5 months. Furthermore, for the linear GBCAs, two classes of Gd species were detected: intact Gd chelate and Gd bound to soluble macromolecules (>80 kDa), whereas, in the case of the macrocyclic GBCA, Gd was detected only in its chelated form 49 . The nature of the macromolecules that bind Gd remains unknown.…”
Section: Gadolinium Location and Speciation In Brain Tissues: Chemicamentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, even a single administration of a clinically‐relevant dose of GBCA demonstrated that linear GBCAs resulted in significantly higher residual Gd concentrations in the cerebellar tissue than a macrocyclic GBCA at the late timepoint of 5 months. Furthermore, for the linear GBCAs, two classes of Gd species were detected: intact Gd chelate and Gd bound to soluble macromolecules (>80 kDa), whereas, in the case of the macrocyclic GBCA, Gd was detected only in its chelated form 49 . The nature of the macromolecules that bind Gd remains unknown.…”
Section: Gadolinium Location and Speciation In Brain Tissues: Chemicamentioning
confidence: 99%
“…Gd speciation in the brain has been the subject of a large number of studies. 24,25,[46][47][48][49] In homogenates of cerebellum from rats treated with linear agents, the presence of soluble macromolecular (250-300-kDa) Gd-containing species was observed 24 days after the last administration, while no such effect was found with macrocyclic GBCAs. Still, in linear GBCAs-treated rats, Gd was found to a large extent in the insoluble brain tissue fraction.…”
Section: Gadolinium Speciation In Brain Tissuesmentioning
confidence: 99%
“…Furthermore, gadolinium compounds can deposit not only in deep grey matter but also in the cerebral cortex. Even one single-use dosage of a GBCA can lead to long-term gadolinium accumulation [41,42].…”
Section: Evidence Of Gadolinium Residues Accumulation In Human Tissuesmentioning
confidence: 99%
“…Linear GBCAs probably undergo partial dechelation and a large portion of gadolinium is retained in the brain, with binding of soluble gadolinium to macromolecules, making clearance potentially impossible. On the other hand, macrocyclic compounds are retained as original chelates and are eliminated over time [42,48,49].…”
Section: Clearance Of Gadolinium From the Brainmentioning
confidence: 99%
“…brain, kidney, liver, muscles, etc.). [9][10][11][12][13][14] One of the most important goals, that of early diagnosis, can therefore be achieved by developing GBCAs that can specifically accumulate at the pathological tissue, via binding to epitopes that identify the tumor cells, even when the disease is at the preliminary stages. This can reduce the dose of GBCAs and improve the diagnostic potential of MRI.…”
Section: Introductionmentioning
confidence: 99%